Paracelsus (Theophrastus Bombastus von Hohenheim, 1493-1541) : essential theoretical writings - Paracelsus, 1493-1541 (Aries book series, 2008)
The daunting writings of Paracelsus-the second largest 16th-century body of writings in German after Luther's-contributed to medicine, natural science, alchemy, philosophy, theology, and esoteric tradition. This volume provides a critical edition of essential writings from the authoritative 1589 Huser Paracelsus alongside new English translations and commentary on the sources and context of the full corpus. The Essential Theoretical Writings incorporate topics ranging from metaphyics, cosmology, faith, religious conflict, magic, gender, and education, to the processes of nature, disease and me.